First aid training with regular school students: experience report (Research, Society and Development, 2021)
Objective: to present a report on the experience of nursing undergraduates in health education on first aid for regular education students. Methodology: Descriptive study based on an account of the experiences lived by undergraduate nursing students during the execution of a scientific initiation project at the State University of Piauí. Developed in a full-time school, from August to October 2019 with a sample of 34 volunteers. It consisted of evaluating the effectiveness of the training through the application of pre- and post-tests followed by educational actions with lectures and dialogue, followed by practical moments of practical moments, where participants were placed in hypothetical situations and needed to intervene. Results and discussion: It was noted the potential for disseminating information that students had, thus facilitating the spread of initial care provided to a victim of accident or sudden illness. Conclusion: It is stated that the learning and experiences achieved were invaluable for the authors of the research.